CYP2J2 and its metabolites (epoxyeicosatrienoic acids) attenuate cardiac hypertrophy by activating AMPKα2 and enhancing nuclear translocation of Akt1 - Wang, Bei (Aging Cell, 2016)
Cytochrome P450 epoyxgenase 2J2 and epoxyeicosatrienoic acids (EETs) are known to protect against cardiac hypertrophy and heart failure, which involve the activation of 5′‐AMP‐activated protein kinase (AMPK) and Akt. Although the functional roles of AMPK and Akt are well established, the significance of cross talk between them in the development of cardiac hypertrophy and antihypertrophy of CYP2J2 and EETs remains unclear. We investigated whether CYP2J2 and its metabolites EETs protected against cardiac hypertrophy by activating AMPKα2 and Akt1. Moreover, we tested whether EETs enhanced cross talk between AMPKα2 and phosphorylated Akt1 (p‐Akt1), and stimulated nuclear translocation of p‐Akt1, to exert their antihypertrophic effects. AMPKα2(−/−) mice that overexpressed CYP2J2 in heart were treated with Ang II for 2 weeks. Interestingly, overexpression of CYP2J2 suppressed cardiac hypertrophy and increased levels of atrial natriuretic peptide (ANP) in the heart tissue and plasma of wild‐type mice but not AMPKα2(−/−) mice. The CYP2J2 metabolites, 11,12‐EET, activated AMPKα2 to induce nuclear translocation of p‐Akt1 selectively, which increased the production of ANP and therefore inhibited the development of cardiac hypertrophy. Furthermore, by co‐immunoprecipitation analysis, we found that AMPKα2β2γ1 and p‐Akt1 interact through the direct binding of the AMPKγ1 subunit to the Akt1 protein kinase domain. This interaction was enhanced by 11,12‐EET. Our studies reveal a novel mechanism in which CYP2J2 and EETs enhanced Akt1 nuclear translocation through interaction with AMPKα2β2γ1 and protect against cardiac hypertrophy and suggest that overexpression of CYP2J2 might have clinical potential to suppress cardiac hypertrophy and heart failure.